Exploring factors affecting Anganwadi workers’ performance motivation: a mixed-methods study in a tertiary care center of central India - Pandey, Snigdha; Patil, Sonali; Narlawar, Uday; Dhumal, Komal (International Journal Of Community Medicine And Public Health, 2024)
Background: The integrated child development services (ICDS) scheme in India employs Anganwadi workers (AWWs) to improve child well-being, reduce health risks, and support maternal education. Despite their crucial role, factors influencing AWWs’ motivation and performance are not well understood. This study examined how individual, program, community, and organizational factors impact AWWs’ motivation in a tertiary care center in central India. Methods: A mixed-methods study was conducted in a tertiary care center in central India, involving 105 AWWs surveyed with a validated questionnaire and 40 AWWs participating in focus group discussions. The study explored individual, community, and health system factors influencing AWWs’ motivation. Results: Results showed that motivation levels were high among 42.85% of AWWs, moderate among 40%, and low among 17.14%. Key motivators included social responsibility, job satisfaction, supportive supervision, and adequate training. However, demotivating factors included inadequate incentives, high workload, insufficient family support, and lack of essential tools and supplies. Conclusions: AWWs’ performance motivation is influenced by a combination of individual, community, and health system factors. Enhancing their motivation requires addressing these factors through targeted interventions such as improved incentives, workload management, better family support, and ensuring the availability of essential tools and supplies. Understanding and addressing these factors can significantly enhance the effectiveness of the ICDS scheme.